Russia’s foreign economic relations with major Latin American partners in the context of anti-Russian sanctions - Vinicio X. Medina Gonzalez; Reyza N. Toro Bellott (Ибероамериканские тетради, 2023)
The article examines key vectors of the development of Russia’s foreign economic relations with its largest trading partners in Latin America in the context of anti-Russian sanctions. The author analyzes peculiarities of Russia’s foreign trade and investment cooperation with Brazil, Ecuador, Argentina, Mexico and Chile. Factors hindering the development of this cooperation are economic instability in the world, anti-Russian sanctions, weak development of logistics networks, lack of free trade agreements, the presence of high custom duties on Russian products in the Latin American market, high competition on part of the United States and China, insufficient interest of Russian business in economic cooperation with the countries of the region over the past decades. It is shown that the largest increase in Russia’s trade turnover with the countries under consideration was recorded with Mexico, an increase in Russian exports was observed in Argentina, and imports - from Mexico. Chile demonstrated the worst indicators in the sphere of foreign trade relations among the countries under consideration. It is concluded that Russia’s largest Latin American partners have serious prospects for expanding their presence on the Russian market in the face of anti-Russian sanctions. Two key factors can be considered favorable for further development of Russia - Latin America trade cooperation. The first one is the orientation of the foreign policy of many countries in the region to other economic partners in order to minimize dependence on the United States. The second one is that Russia is shifting its vectors of economic cooperation from unfriendly countries to other countries, including Latin American states. It is concluded that investment cooperation between the countries has certain prospects for development, especially in the field of oil and gas exploration, energy and railway construction.